A CORPUS-BASED OF CRITICAL DISCOURSE ANALYSIS REGARDING “GOVERNMENT SUPPORT” AT THE FORMULA-E INDONESIA - Aal Inderajati; Ahmad Zaidi; Anandya Asprillia (Universitas Pamulang, 2023)
Formula-E, which was successfully held in Jakarta, Indonesia, gave rise to various reports. This linguistics study aims to analyze the purpose of online media coverage about 'dukungan pemerintah' on the Formula-E event, which took place on Saturday, 4 June 2022. The data were taken from online media portals Bisnis.com, CNN, Detik, Kompas, Pikiran Rakyat, and Tribunnews. There are 108 articles analyzed in this study. The articles were scrapped from the same day when the Formula E was held. The data that are sentences from the articles were analyzed using a corpus approach to find words 'dukungan’ (support) and 'pemerintah' (government) using concordances. The data discussed using Van Dijk's critical discourse analysis theory to reveal its meaning. The results found that the macrostructure is government support for the 2022 Formula-E. Then the superstructure of the six media uses a framework that matches the title and content. In the microstructure, 'dukungan' and 'pemerintah' concordances were found. Analysis of social cognition found that online media portals show partiality. The media that is most likely to support the government is CNN. It can be seen from the chosen language, which tends to provide evidence that the central government has supported this event. Meanwhile, the media that seemed to criticize the government's support was Tribunnews by presenting the figure of Joko Suranto as one of the Indonesian citizens who sponsored this event rather than central government. The social context to be achieved is that online media tend to show their side with the government by not choosing words that discredit the government.